Capability of Activity Planning Based on Organizational Citizenship Behavior to Accelerate Development - Muhamad Taher Rumoning; Sundjoto Sundjoto; Titis Istiqomah; Untung Tamsil (PT. BATARI EDU CALYA, 2025)
The research aims to determine the capability factors of regional development activity planners in Fakfak Regency. The vast area of the district and the many technical problems for regions in Indonesia's frontier, outermost and underdeveloped regions; requires equitable and targeted development planning to accelerate economic development. Combination research with a qualitative-quantitative-qualitative design was carried out during 2023. Data was obtained through closed interviews using a questionnaire tool. The question grid in the questionnaire refers to the standard target answers, so that respondents' answers can be given a weight value. Weighting uses a scale of 1-10. Test the validity of the answers using the cross triangulation technique. The interview data was then analyzed using the SPSS statistical tool. The qualitative analysis description reviews the regression model based on the results of the analysis of the coefficient of determination (R-square). The research results show that the capabilities of development planners including: competence, integrity, innovation, motivation and empathy still need to be improved in order to achieve accelerated development evenly in Fakfak district. Budget planners still need to train themselves to be more focused on achieving the vision, mission and goals of the Fakfak Regency Government by implementing organizational citizenship behavior (OCB)